Successful management of tracheal lobular capillary hemangioma with arterial embolization followed by electrosurgical snaring via flexible bronchoscopy in an 11-year-old boy: A case report and literature review - Tao, Xiaofen; Wu, Lei; Li, Shuxian; Wu, Yuxin; Lai, Can; Chen, Enguo; Chen, Zhenjie; Jin, Guoping; Wang, Yingshuo (Frontiers in Medicine, 2023)
Lobular capillary hemangioma (LCH), previously known as pyogenic granuloma, is a benign vascular lesion and commonly found within the oral and nasal cavity. However, it is rarely encountered within the trachea, especially in pediatric patients, which presents with hemoptysis, cough, and wheeze, and are frequently misdiagnosed as bronchitis or asthma. Limited literatures are known about the presentation, behavior, and management of tracheal LCH. Herein, we describe a rare case of tracheal LCH in an 11-year-old boy with a history of hemoptysis, which was successfully managed with arterial embolization followed by electrocautery loop snaring via flexible bronchoscopy. No complication occurred during and after the procedure. A review of the relevant literature is also provided. Our case is unique, given the therapeutic strategy utilized for pediatric tracheal LCH and reminds physicians to be aware of tracheal LCH in the differential diagnosis for hemoptysis.